The Effect of Green Accounting on Financial Performance with Corporate Social Responsibility (CSR) as Mediation - Asti, Noviolita Lingga; Aulia, Yoosita (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : This study aims to determine the effect of green accounting on financial performance with corporate social responsibility (CSR) as a mediating variable in energy sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Design/Methode/Approach : This research is a type of quantitative research that uses secondary data in the form of company reports and company sustainability reports. This study used a sample of 12 companies in the energy sub-sector. The analytical tools used in this research are regression and pathy analysis. Research Finding : Based on the results of data analysis, the research findings are (1) green accounting has an effect on financial performance; (2) green accounting has an effect on corporate social responsibility (CSR); (3) corporate social responsibility (CSR) has no effect on Financial Performance; (4) corporate social responsibility (CSR) is not able to mediate the influence between green accounting on financial performance. Theoretical contribution/Originality : The results of this study indicate a lack of alignment with the grand theory used, namely the legitimacy theory as well as previous research. Examining the influence of green accounting on financial performance with corporate social responsibility (CSR) revealed that CSR was not able to mediate the relationship. Practitionel/Policy implication : The research findings on one of the hypotheses indicate that green accounting has an impact on financial performance. This finding has implications for all companies; by adopting green accounting, companies demonstrate a commitment to social and environmental responsibility, which can help maintain stakeholders' trust. It can also facilitate the company in attracting future investors. Research limitation : The limitation of this research is that the number of samples used is relatively minimal. Out of 80 companies, only 12 companies from the energy sub-sector reported their corporate social responsibility activities in the annual report. Therefore, the possibility of bias in the research results in each article is still relatively significant.